'Subjectless' Subjectivity: Anscombe and Sartre on Self-Consciousness. - Li, Zhihan (Problems / Problemos, 2025)
Anscombe famously argues that 'I' is not a referring expression, otherwise, a 'Cartesian Ego' would inevitably appear. She thinks the form of self-consciousness expressed in 'I' is 'subjectless': it is consciousness that does not involve a self-object (or Ego). Sartre's theory of consciousness offers a strikingly parallel and mutually illuminating framework. He similarly denies the presence of the Ego within consciousness, arguing instead that the Ego is a transcendent object constructed through reflection. For both of them, the fundamental form of self-consciousness is pre-reflective. I argue that Anscombe's position encounters two difficulties: (1) how the non-referential 'I' can express subjectivity, and (2) how self-consciousness is about an embodied subject. I propose that Sartre's accounts of (1) the 'fundamental ipseity' and (2) the 'lived body' offer a phenomenological framework that helps to respond to Anscombe's difficulties.